Segunda infância e a educação natural em Jean-Jacques Rousseau - Santos, Almir Paulo dos (2008)
The investigation, goal of the current exposition, approaches the concept of second childhood in the second book from the literary composition Emílio or from Education by Jean-Jacques Rousseau. The center of such concept rests on the strengthening of the body and in the refining of the senses and, to justify it, Rousseau appeals to the ancient tradition, combining in his natural education project well defined ethic - cosmological aspects from that tradition. It restores, first, nuclear aspects of that tradition, making evident, from Platão and Sêneca, the rational and kind cosmos unit. Next, it faces these ethic-cosmological results with the rousseauniana childhood bonds thesis with the thought of humanity inserted in a cosmic order. This confront creates the background through which the arguments developed in favor of the strengthening of the body and refining of the senses are analysed in details. Finally, the last part, concerns in the reflection on the moral implications of this analyses for the natural education project. The main idea that passes by all the chapters consists on showing that the natural education project formulated to the second childhood rests on the normative sense of nature, which is based upon a ethic-cosmological order resulted from the greek-roman tradition, but that takes over a modern external appearence in the thought of Rousseau. Although he has made good use of this long tradition, Rousseau inovates the concept of childhood, criticizing the reduction of the child to a small imperfect adult and defending the pedagogical significance of conceiving it in his own world